Managing Lymphoma with Non-FDG Radiotracers: Current Clinical and Preclinical Applications. (6th June 2013) - Kong, Fan-Lin; Ford, Richard J.; Yang, David J.
Abstract : Nuclear medicine imaging modalities such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT) have played a prominent role in lymphoma management. PET with [ 18 F]Fluoro-2-deoxy-D-glucose (FDG) is the most commonly used tool for lymphoma imaging. However, FDG-PET has several limitations that give the false positive or false negative diagnosis of lymphoma. Therefore, development of new radiotracers with higher sensitivity, specificity, and different uptake mechanism is in great demand in the management of lymphoma. This paper reviews non-FDG radiopharmaceuticals that have been applied for PET and SPECT imaging in patients with different types of lymphoma, with attention to diagnosis, staging, therapy response assessment, and surveillance for disease relapse. In addition, we introduce three radiolabeled anti-CD20 antibodies for radioimmunotherapy, which is another important arm for lymphoma treatment and management. Finally, the relatively promising radiotracers that are currently under preclinical development are also discussed in this paper.